Colonial Legislation and the Erosion of Brahmanic Dominance: Transforming the Caste System in British India - Dr. Bashir Ahmed Kalwar; Dr. Taha Shabbir; Dr. Sayed Shujaudin; Dr. Phuloo Sunder Meghwar; Manzoor Ahmed Kalwar; Asif Ali Kunbhar (Dialogue Social Science Review (DSSR), 2025)
This research investigates how British colonization has transformed the caste system, particularly the collapse of Brahmanism in the Indian Subcontinent. British authorities introduced specific legal reforms like, The Abolition of Sati Act 1829, The Caste Disabilities Removal Act 1850, and The Hindu Widow's Remarriage Act 1856 that challenged the Brahmanic caste system. The role of colonialism and changing hierarchies is analyzed through archives, political commentary, and the reformist writings of figures such as Ram Mohan Roy, Jyotirao Phule, and B.R. Ambedkar. Moreover, this study seeks to understand the impacts of British colonialism on the Brahmanic orthodox psyche. Further, this paper discusses how the above legislatures related to the Brahmanic caste order, their role in discrimination along the lines of caste, imposition of social boundaries, and the politics of colonial India. New caste identities were formalized to subtend traditional limits of caste authority. This research will be a motivation for the depressed classes of the Indian subcontinent to reconsider their policies to work on getting more rights in the post-colonial era.